Poor treatment outcomes of acute exacerbations of chronic obstructive pulmonary disease and their associated factors among admitted patients in East Gojjam, 2023 - Getnet, Melaku Tadele; Afenigus, Abebe Dilie; Gete, Menberu; Emrie, Ambaw Abebaw; Tsegaye, Dejen (Frontiers in Medicine, 2024)
Background: Acute exacerbation of chronic obstructive pulmonary diseases is a major public health challenge in the world, resulting in significant health and economic burden. There is no adequate study has been conducted in Ethiopia so far on poor treatment outcome of acute exacerbation of chronic obstructive pulmonary diseases. Objective: To assess poor treatment outcome of acute exacerbation of chronic obstructive pulmonary disease and its associated factors among admitted patients in East Gojjam, 2023 Design: Institutional based cross-sectional study design was employed. Methods: Institutional based cross-sectional study design was employed from April 7, 2023 to May 7, 2023 among 384 participants which were selected using simple random sampling technique. The data were extracted from patient chart and registers. Data were entered into epi data and analyzed using SPSS version 26 software. Binary logistic regression was used for analysis to identify the association between the dependent and independent variables. Variables with P-value < 0.25 in the bivariable logistic regression was used as a candidate for multivariable logistic regression and those variables with p-value <0.05 were considered statistically significant. Results: From a total of 346 patients, 99(28.6%) (95% CI, 23.9-33.3) developed poor treatment outcome of exacerbation of chronic obstructive pulmonary diseases. Age 65 years and above (AOR=3.9; 95% CI: 1.57- 9.71), having comorbidity illness (AOR=2.6; 95% CI: 1.287-5.20), length of hospital stay greater than 7 days (AOR=3.9; 95% CI: 1.97-7.70) and low oxygen saturation (<88%) (AOR=9.0; 95% CI: 4.43-18.34) were variables significantly associated with poor treatment outcome. Conclusion: Nearly one-third of the patients treated with acute exacerbation of chronic obstructive pulmonary diseases at Debre Markos comprehensive specialized hospital experienced poor treatment outcomes. There is a significant association between poor treatment outcome of acute exacerbation of chronic obstructive pulmonary diseases and age ≥65 years, having comorbidities, prolonged hospital stays and low oxygen saturation.